2000
DOI: 10.1152/ajprenal.2000.278.3.f380
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of renal ischemic preconditioning and adenosine pretreatment: role of A1 and A3receptors

Abstract: Renal ischemia and reperfusion during aortic and renal transplant surgery result in ischemic-reperfusion injury. Ischemic preconditioning and adenosine infusion before ischemia protect against ischemic-reperfusion injury in cardiac and skeletal muscle, but these protective phenomena have not been demonstrated in the kidney. Rats were randomized to sham operation, 45-min renal ischemia, ischemic preconditioning with four cycles of 8-min renal ischemia and 5-min reperfusion followed by 45-min renal ischemia, sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
181
2
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(198 citation statements)
references
References 48 publications
11
181
2
4
Order By: Relevance
“…Hence, dual acting agonists for A 1 and A 3 ARs might be useful for cardioprotection. In contrast to the effect of AR activation on the heart, pretreatment with an A 1 agonist or an A 3 antagonist protects the kidney from a subsequent prolonged ischemic insult [28]. The role of the A 3 AR in kidney function was further confirmed by the fact that A 3 AR knockout mice are protected against ischemia-and myoglobinuria-induced renal failure [29].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, dual acting agonists for A 1 and A 3 ARs might be useful for cardioprotection. In contrast to the effect of AR activation on the heart, pretreatment with an A 1 agonist or an A 3 antagonist protects the kidney from a subsequent prolonged ischemic insult [28]. The role of the A 3 AR in kidney function was further confirmed by the fact that A 3 AR knockout mice are protected against ischemia-and myoglobinuria-induced renal failure [29].…”
Section: Discussionmentioning
confidence: 99%
“…In kidneys subjected to ischemiareperfusion injury, preischemic administration of A 1 adenosine receptor agonists induced ischemic preconditioning, whereas postischemic A 2A adenosine receptor activation reduced tissue injury by attenuating the reperfusion phase of the injury process (6,9,10). Unlike A 1 or A 2 receptor agonists, A 3 adenosine receptor activation before renal ischemia worsened renal ischemia-reperfusion injury, whereas antagonism of A 3 adenosine receptors protected renal function (9).…”
mentioning
confidence: 99%
“…Our laboratory previously showed that exogenous and endogenous A 1 adenosine receptor (A 1 AR) activation protected against renal IR injury in mice 8,9 as well as in rats 10,11 with reduced renal tubular necrosis, apoptosis, and inflammation. Moreover, endogenous A 1 ARs have an important role in protecting the liver against IR injury in mice.…”
mentioning
confidence: 99%